A numerical study on the creation of artificial supercritical geothermal reservoirs by hydraulic fracturing. (November 2022) - Watanabe, Kimio; Watanabe, Norihiro; Watanabe, Noriaki; Sakaguchi, Kiyotoshi; Aichi, Masaatsu; Ouchi, Hisanao; Asanuma, Hiroshi
Highlights: Hydraulic fracturing at supercritical temperatures could create meaningful sized artificial reservoirs. In-situ stress conditions and pre-existing weak faces have a significant impact on the progression of the stimulated zone. The position of the artificial reservoir may be controlled by forming a weak face before stimulation. The injection of cold water may not prevent the creation of cloud-fracture networks. The use of a short open-hole section in injection wells may be effective in reducing the time and amount of water. Abstract: We developed a supercritical geothermal reservoir creation simulator that uses a simple 3D model. The simulator was based on an increase in permeability caused by hydraulic fracturing as confirmed in a laboratory experiment. The simulator does not simulate the fracture behavior in rocks; instead, the fracturing phenomenon is expressed as a rapid change in permeability. In this study, we evaluated rock mechanics such that changes in crustal stress associated with changes in pore pressure could be considered. Using the developed simulator, a simulation was performed for the creation of a reservoir using hydraulic fracturing. The results showed that a target artificial reservoir with a radius of hundreds of meters could be formed through hydraulic fracturing. Furthermore, the state of the initial crust stress had a major impact on reservoir creation.